Using deliberative foresight to envision a neo-carbon energy innovation ecosystem – a case study of Kenya - Joni Karjalainen; Sirkka Heinonen (Taylor and Francis Ltd., 2022)
Foresight is a pragmatic futures studies approach as structured debate about future-related topics. Deliberative foresight addresses stakeholders affected by specific futures. This paper goes beyond a low-carbon strategy to present the potential of futures based on renewable energy. In the neo-carbon energy system, high shares of solar, wind, and other renewables are used, and carbon dioxide from the air is used as a source for synthetic products such as plastics, chemicals and medicine. As transitions are about technological and social change, a neo-carbon energy innovation ecosystem, consisting of actors at multiple levels, is envisioned. To represent the present ‘direction’ of Kenya's energy transition, four renewable energy approaches and projects are examined. A conceptual model, which consists of deliberative foresight, innovation ecosystems thinking, transformative potential and sustainability, is then introduced. To study emerging energy transformations, historical assumptions and conventional approaches to development and scenario-making need to be challenged. This paper claims that deliberative foresight and a systemic approach to innovation can enable African countries to examine how their economies and energy systems can be transformed into emissions-free, efficient, low-cost, and sustainable. Our approach emphasizes inclusive innovation, broad-based socio-economic benefits, and minimizing environmental harm.